The micro-macro link in heterodox economics - Claudius Gräbner-Radkowitsch; Jakob Kapeller (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
At its core, the discussion on the micro-macro link in heterodox economics is concerned with the correct treatment of aggregates and aggregation in social theory. In this chapter we survey heterodox approaches to the micro-macro link with a focus on shared understandings and convictions that apply across different schools of thought. In addition, we illuminate typical fallacies related to the treatment of aggregation and aggregates as well as the philosophical underpinnings of heterodox ontology to better understand conceptual differences between heterodox economics and competing approaches. Given that economics faces myriad problems of aggregation - as in the case of market interaction, macroeconomic aggregates, or interpersonal coordination and contracting - the quest to provide suitable conceptual tools and philosophical foundations to adequately address aggregates and aggregation should be of special interest to economists of different persuasions.
Keywords: 330